Self-Actualization and Stress Resistance: Methodological and Practical Aspects of Studying the Personality of Students in the Process of Distance Learning - Gevorgyan, Srbuhi; Berberyan, Asya; Berberyan, Hermine (Տիգրան Մեծ)
The article considers the issues of studying the self-actualization of the personality by the representatives of various conceptual schools. We consider distance learning in the higher education system as a capacity for opportunities, as the implementation of an individual approach in learning, motivating the student to self-learn, freedom from rigid binding to the territory and a certain period of time, objective assessment of learning results. The study‟s goal is to investigate the connection between the selfactualization of the personality and the level of students‟ stress resistance in the process of distance learning. Research methods: questionnaires and testing. Based on theoretical analysis, the methodological basis of the study was determined in relation to the self-actualization of the personality as the highest level of its development in the context of humanistic psychology, distance learning. As a result of an empirical study, the authors of the article revealed the correlation between the ambition for self-actualization and the level of stress resistance. The ambition for self-actualization correlates with the level of assessment of one‟s effectiveness in distance learning, and there are sex differences according to the criteria of the ambition for self-actualization and the level of stress resistance.
Keywords: Philosophy of education